Muscle force contributions to ankle joint contact forces during an unanticipated cutting task in people with chronic ankle instability. (19th July 2021) - Kim, Hoon; Palmieri-Smith, Riann; Kipp, Kristof
Abstract: The purpose of this study was to compare muscle force contributions to ankle joint compression and anteroposterior shear forces between people with chronic ankle instability (CAI) and healthy controls (CON) during an unanticipated cutting task. Eleven people with CAI and 11 CON performed an unanticipated cutting task as three-dimensional motion capture, ground reaction force (GRF), and muscle activation data were collected. A musculoskeletal modeling was used to calculate talocrural joint compression and anteroposterior shear forces and parse out the contributions to these forces from ankle-spanning muscles and from GRF. Independent t-tests were used for statistical analysis. People with CAI exhibited greater anterior shear force peaks during early ( p = 0.048, d = 0.98) and late ( p = 0.017, d = 1.21) stance compared to CON. The difference in early stance shear force appeared to arise from greater GRF contribution ( p = 0.026, d = 1.12) in CAI group, whereas the difference in late stance shear force appeared to arise from greater contribution of lateral gastrocnemius ( p = 0.026, d = 1.12), medial gastrocnemius ( p = 0.048, d = 0.98), tibialis posterior ( p = 0.017, d = 1.22), fibularis brevis ( p = 0.035, d = 1.05), and fibularis longus ( p = 0.023, d = 1.15). People with CAI exhibit greater anterior shear, but not compressive forces in talocrural joint during an unanticipated cutting task. The differences in anterior shear force were the result of passive and active contributions from GRF during early stance and lower leg muscles during late stance, respectively.